2009
DOI: 10.1002/app.29741
|View full text |Cite
|
Sign up to set email alerts
|

Expanded graphite–epoxy composites with high dielectric constant

Abstract: Composites of an expanded graphite/diglycidyl ether of bisphenol A (DGEBA) were prepared by a simple melt blending method, and their dielectric and mechanical properties were investigated. During observations of fractured surfaces of the composites, the graphite sheets were seen to be homogeneously dispersed in the epoxy matrix. Moreover, the composites presented an enhanced dielectric constant ($ 180) and a low loss factor ($ 0.05) at 50 Hz, suggesting their potential suitability for embedded dielectric appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…And the in‐plane Young's modulus and electrical conductivity of graphite is close to those of CNT . Several reports have been published on the dielectric properties of polymer‐based composites containing modified graphite . For example, Min et al fabricated expanded graphite/epoxy composites with a high dielectric constant of 240 and a dielectric loss of 5 at 1kHz .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…And the in‐plane Young's modulus and electrical conductivity of graphite is close to those of CNT . Several reports have been published on the dielectric properties of polymer‐based composites containing modified graphite . For example, Min et al fabricated expanded graphite/epoxy composites with a high dielectric constant of 240 and a dielectric loss of 5 at 1kHz .…”
Section: Introductionmentioning
confidence: 95%
“…For example, Min et al fabricated expanded graphite/epoxy composites with a high dielectric constant of 240 and a dielectric loss of 5 at 1kHz . Xie et al investigated expanded graphite/epoxy composites and found that the composites presented an enhanced dielectric constant (120) and a low loss (0.3) at 1 kHz suggesting their potential suitability for embedded dielectric applications . Xie et al investigated the preparation and dielectric behavior of PVDF composite filled with stearic acid modified graphite nanoplatelet .…”
Section: Introductionmentioning
confidence: 99%
“…When the epoxy resin (epoxy) is cured by the curing agent, it forms three-dimensional network structure inside, which has a good corrosion resistance, excellent mechanical strength, excellent processing performance, low shrinkage characteristics and so on, but also with lower permittivity, which is about 4.6-5.0 1 and hinders epoxy 's practical application of high dielectric constant. Two or more single-phase materials are composited to modify single-phase materials through taking advantage of the complementary of each material 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the GIC route, graphite was dispersed in concentrated sulfuric acid and nitric acid in a ratio of 4:1. The following thermal expansion at high temperatures led to expanded graphite which was used as a filler in several polymers like polystyrene, polyethylene, poly(propylene), polyamide 6, poly(phenylene sulfide), epoxy resin, and more 7–33. The resulting composites based on a conventional melt compounding process exhibit a good dispersion of expanded graphite resulting in low rheological or electrical percolation threshold and increased stiffness.…”
Section: Introductionmentioning
confidence: 99%